PERAN ORANG TUA DALAM PEMBELAJARAN DARING PADA SEKOLAH DASAR BATURETNO 01 DAMPIT - Inda Purwati; Devi Wahyu Ertanti; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The purpose of this study was to determine the role of parents in online learning as a substitute for teachers; In grade 5 baturetno state elementary school 01 Dampit. By using a population of all parents of 5 th grade stuudebts as many as 18 people as the population. Then the sample was taken students of the class 5. The data collection technique in this study uses observation, interviews, and documentation to obtain data and then processed it. The results in this study indicate that the role of perents in online learning in grade 5 baturetno 01 Dampit state elementary school knows their role of parents and as substitute teachers when at home daring online learning, as a motivation and, as a facilitator. The results of the previous data description have shown that the role of the parents in online learning includes: a) the role of parents as teachers, b) the role of parents as motivators, c) the role of a role as teacher at home, whare parents educate and can guide their children in leasrning remotely from home. 1. Parents as facilitators, namely parents as facilities and onfrastructure like their children in implementing distance learning, 2. Parents as motivators, namely parents can provide encouragement out learning, so that children have the enthuasiasm to learn, and get good achivements, 3. parents as influence, parents have a role to always guide their children in order to achieve success in the future. Parents also play a role in directing children according to the talents and interests of each child. This is because have different talents. Children have the right to realize their dreams. Children must always be reminded not to get. Involved in an uncertain school holiday situation like today.